Proteotyping of Holm Oak (Quercus ilex subsp. ballota) Provenances Through Proteomic Analysis of Acorn Flour (Methods in Molecular Biology Plant Proteomics SE - 49, 2014)
Proteomics has become a powerful tool to characterize biodiversity and natural variability in plant species, as well as to catalogue and establish phylogenetic relationships and distances among populations, provenances or ecotypes. In this chapter, we describe the standard proteomics workflow that we currently use in cataloguing Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) populations. Proteins are extracted from acorn flour or pollen by TCA/acetone or TCA/acetone-phenol methods, resolved by one- or two-dimensional gel electrophoresis, and gel images are captured and analyzed by appropriate software and statistical packages. Quantitative or qualitative variable bands or spots are subjected to MS analysis in order to identify them and correlate differences in the protein profile with the phenotypes or environmental conditions.